ANALISIS PAJAK HOTEL DI KABUPATEN KOTAWARINGIN TIMUR - Novia Dwi Putri; Idah Zuhroh; Hendra Kusuma (Jurnal Ilmu Ekonomi JIE, 2018)
Research entitled "HOTEL TAX ANALYSIS IN EAST KOTAWARINGIN REGENCY".This study aims to find out the Hotel Tax Analysis In Kotawaringin Timur District. Method of data analysis tool used in this research is panel data analysis. The results of this study indicate that the number of hotels (X1) has a positive relationship to the hotel tax revenue. Elasticity value is 0.834700, meaning the increase in the number of hotels will increase the hotel tax revenue of 0.834700 and cateris paribus. Population (X2) has a positive relationship to the hotel tax revenue. Elasticity value is 0.809850, meaning the decrease in population will increase the hotel tax revenue of 0.809850 and cateris paribus. Place of Attraction (X3) has a positive relationship to the increase in hotel tax revenue is known by its elasticity of 0.527667 which will significantly affect the hotel tax revenue.Keywords: Tax, Hotel, Places of Interest.